2022
DOI: 10.1037/tra0001188
|View full text |Cite
|
Sign up to set email alerts
|

The mental health effects of the COVID-19 pandemic on children and adolescents: Risk and protective factors.

Abstract: Objective: The restrictions to contain the coronavirus disease 2019 (COVID-19) pandemic have led to considerable social isolation, posing significant threats to mental health worldwide. The preventive lockdowns may be especially difficult for children and adolescents, who rely extensively on their daily routines and peer connections for stability and optimal development. However, there is a dearth of longitudinal research examining the mental health and daily life impact of the pandemic among children and adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 24 publications
(27 reference statements)
4
69
0
2
Order By: Relevance
“…The pandemic and the confinement measures have had their effect on youngsters; a study conducted by Shoshani and Kor (2021) revealed a significant increase in psychological distress and mental health symptoms among school-aged children compared to the pre-pandemic baseline. However, to our best knowledge, no study has yet to examine the effect of the pandemic on risk behaviors of adolescents in Israel [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pandemic and the confinement measures have had their effect on youngsters; a study conducted by Shoshani and Kor (2021) revealed a significant increase in psychological distress and mental health symptoms among school-aged children compared to the pre-pandemic baseline. However, to our best knowledge, no study has yet to examine the effect of the pandemic on risk behaviors of adolescents in Israel [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reduced family routines, specifically bedtime and screen time routines, during COVID-19 may negatively affect adolescents’ health behaviors [ 40 ]. This reduction impacts adolescents’ daily functioning in terms of more sleepiness, problems related to falling asleep and waking up, and more fatigue [ 35 , 36 ], contributing to attention problems, lower academic productivity/achievement, behavioral and emotional problems, [ 41 ] and decreases in subjective well-being [ 42 ]. Although family routines were difficult to maintain in the context of the pandemic, they were associated with better individual and family well-being during this period of acute health, economic, and social stress [ 40 ].…”
Section: Results On the Rationale And The Construction Processmentioning
confidence: 99%
“…Findings on the impacts of containment measures in terms of everyday hassles, physical and mental health crises, escalating violence, and diminished social support affirm prior scholarship questioning assumptions that homes are a one-dimensional source of safety, comfort, and ease (Mallett 2004 ). Yet scholars have also pointed to the protective effects of being anchored to home during the pandemic (Ahrens et al 2021 ; Shoshani and Kor 2021 ). Even (or especially) amid a global crisis, homes still offer peace, comfort, recreation, learning, social support, communication, and positive identity formation (Ahrens et al 2021 ; Panchal et al 2021 ; Shoshani and Kor 2021 ).…”
Section: Place-based Impacts Of Covid-19mentioning
confidence: 99%
“…Yet scholars have also pointed to the protective effects of being anchored to home during the pandemic (Ahrens et al 2021 ; Shoshani and Kor 2021 ). Even (or especially) amid a global crisis, homes still offer peace, comfort, recreation, learning, social support, communication, and positive identity formation (Ahrens et al 2021 ; Panchal et al 2021 ; Shoshani and Kor 2021 ). The pandemic has thus not entirely shifted our understandings of home.…”
Section: Place-based Impacts Of Covid-19mentioning
confidence: 99%